2014
DOI: 10.1590/1981-8637201400020000072608
|View full text |Cite
|
Sign up to set email alerts
|

Different materials and techniques for accurate molding for adaptation in angled implants

Abstract: Objective To evaluate the marginal misfit between intermediate and micro-unitmetal cylinder, by varying the angle of the implants, using two different types of material and different molding techniques. Methods A model was made with three implants (one perpendicular to the horizontal plane and two inclined) using micro-unit intermediates. A rod attached to the master model served as a control condition to evaluate the suitability of the twenty specimens, carried out with the help of an optical stereomicroscope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Regarding the precision of the techniques, this study showed no significant differences between the technique groups. Other authors have also shown that the open‐ and closed‐tray techniques exhibit no significant differences; however, some studies have reported higher accuracy of the open‐tray conventional technique. Although our study did not demonstrate a difference between the techniques, accuracy is a highly controversial subject in the literature.…”
Section: Discussionmentioning
confidence: 95%
“…Regarding the precision of the techniques, this study showed no significant differences between the technique groups. Other authors have also shown that the open‐ and closed‐tray techniques exhibit no significant differences; however, some studies have reported higher accuracy of the open‐tray conventional technique. Although our study did not demonstrate a difference between the techniques, accuracy is a highly controversial subject in the literature.…”
Section: Discussionmentioning
confidence: 95%